METODE OUTDOOR STUDY DALAM PEMBELAJARAN PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI PADA SISWA KELAS III DI SD NEGERI TULANGAMPIANG KECAMATAN DENPASAR UTARA, KOTA DENPASAR - I Ketut Winantra; Ni Made Surawati; Ni Putu Yuni Diantari (UNHI PRESS, 2021)
Education is a process that is carried out consciously, systematically, planned, directed to develop the potential that students have in order to benefit themselves and their nation. Teachers have an important role in education, namely as facilitators and motivators who facilitate students in the learning process . Teachers must be able to choose appropriate learning methods in the teaching and learning process. Interests of learners would increase if the learning process fun and not saturated, with the implementation of the method of outdoor study learners will be invited directly to the field to observe and practice the be In relation to teaching materials , students are able to fully understand Hindu religious learning in everyday life . So that the results of this learning are very useful for students.